Statistical thinking : improving business performance - Hoerl, Roger Wesley, 1957-; Snee, Ronald D. (Wiley SAS business series, 2020)
"This book will help managers who are undertaking improvement initiatives (six sigma, balanced scorecard, etc.) in their business understand the "why" and "what" of statistics (i.e., what we are trying to accomplish and the role that statistics can play) prior to getting into the "how" (i.e., statistical techniques). Performance management initiatives require statistical knowledge in order to understand these process improvement tools. This book will provide the foundation that managers will need"--